Pengaruh Audit Commite, Kualitas Audit, dan Whistleblowing System terhadap Tindakan Pencegahan Fraud - Asma Nadia Fathu Rahmah; Nedi Hendri; Ana Septiani (Universitas Muhammadiyah Metro, 2026)
This research aims to determine the influence of the Audit Committee, audit quality, and whistleblowing system on fraud prevention measures in transportation and logistics companies listed on the Indonesia Stock Exchange. This research method uses a quantitative approach, with the population being transportation and logistics companies listed on the Indonesia Stock Exchange, specifically 37 companies, and a sample of 14 companies × 3 periods. The data analysis technique uses descriptive statistical analysis and multiple regression analysis techniques as the main methods. The analysis process involves classical assumption tests and hypothesis tests. Data were processed using SPSS version 26. The results of this study show that the Audit Committee significantly affects Fraud Prevention, Audit Quality significantly affects Fraud Prevention, the Whistleblowing System significantly affects Fraud Prevention, and the Audit Committee, Audit Quality, and Whistleblowing System simultaneously significantly affect Fraud Prevention.